Environment conscious manufacturing - Gupta, Surendra M. (CRC Press, 2008)
Hotter temperatures, less arctic ice, loss of habitat-every other day, it seems, global warming and environmental issues make headlines. Consumer-driven environmental awareness combined with stricter recycling regulations have put the pressure on companies to produce and dispose of products in an environmentally responsible manner. Redefining industrial ecology, while reconsidering the original definition, Environment-Conscious Manufacturing explores topics such as industrial metabolism, product design for the environment, design of reverse and closed-loop supply chains, and disassembly modeli.
Keywords: Manufacturing processes -- Environmental aspects.; Engineering design -- Environmental aspects.; Industries -- Environmental aspects.; Waste minimization.; Source reduction (Waste management); elektronické knihy; electronic books